PERAN PROVINSI KEPULAUAN BANGKA BELITUNG DALAM PENGEMBANGAN SISTEM EKONOMI KERAKYATAN SAAT PANDEMI COVID-19 MENURUT UNDANG-UNDANG 1945 - Muhamad Hijran; Dini Oktariani (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
This research study aims to determine the Strategy for the development of a People's Economy (Economic Civic) and is very relevant to do considering that the People's Economy is businesses in the economic field, where the main achievement target is not financial gain. This study uses qualitative research methods, namely collecting data from scientific articles, research reports or other matters relevant to the topic. The results of the study conclude that UMKM in the role of the populist economy in the Province of the Bangka Belitung Islands through entrepreneurial programs, business unit development, improving the quality of human resources, and utilizing technology and information so taht they can have a positive impact on increasing products.